The Road to Differentiation in Slovenia - Klemencic, Manja; Komljenovic, Janja (International Higher Education, 2011)
While diversity of higher education institutions is in principle almost unanimously viewed as a favorable condition, the mechanisms to achieve it are the source for much contention. Positive financial incentives ("carrots") are proving to be more politically palatable, and hence easier to implement, than negative financial measures ("sticks"). The article describes the case of Slovenia, where the government has proposed positive financial incentives to achieve two goals: to reward excellence, but also to "shape-up" the least successful institutions, and, thus, instigated institutional diversification in Slovenian higher education.